Brain Microglial Activation Increased in Glucocerebrosidase (GBA) Mutation Carriers without Parkinson's disease. Issue 3 (5th December 2020) - Mullin, Stephen; Stokholm, Morten Gersel; Hughes, Derralyn; Mehta, Atul; Parbo, Peter; Hinz, Rainer; Pavese, Nicola; Brooks, David J.; Schapira, Anthony H.V.
ABSTRACT: Background: Glucocerebrosidase gene mutations are a common genetic risk factor for Parkinson's disease. They exhibit incomplete penetrance. The objective of the present study was to measure microglial activation and dopamine integrity in glucocerebrosidase gene mutation carriers without Parkinson's disease compared to controls. Methods: We performed PET scans on 9 glucocerebrosidase gene mutation carriers without Parkinson's disease and 29 age‐matched controls. We measured microglial activation as 11 C‐( R )‐PK11195 binding potentials, and dopamine terminal integrity with 18 F‐dopa influx constants. Results: The 11 C‐( R )‐PK11195 binding potential was increased in the substantia nigra of glucocerebrosidase gene carriers compared with controls (Student t test; right, t = −4.45, P = 0.0001). Statistical parametric mapping also localized significantly increased 11 C‐( R )‐PK11195 binding potential in the occipital and temporal lobes, cerebellum, hippocampus, and mesencephalon. The degree of hyposmia correlated with nigral 11 C‐( R )‐PK11195 regional binding potentials (Spearman's rank, P = 0.0066). Mean striatal 18 F‐dopa uptake was similar to healthy controls. Conclusions: In vivo 11 C‐( R )‐PK11195 PET imaging detects neuroinflammation in brain regions susceptible to Lewy pathology in glucocerebrosidase gene mutation carriers without Parkinson's. © 2020 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society